2009
DOI: 10.1007/s11218-009-9099-x
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel model of educational expectations of secondary school students in the United States

Abstract: Using the Educational Longitudinal Survey of 2002, we investigate variation in factors that contribute to Asian, Black, Hispanic, and White students' educational expectations. Separate multilevel models demonstrate group variation in student and school-level influences. Academic and school factors explained the most variation in White students' expectations. School characteristics were least predictive of Black student expectations. For Hispanic students, the overall influence of family socioeconomic status (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Recent studies have found that parents affect their children's expectations through their own educational background, SES, and expectations for their children (Lowman & Elliott, 2010; St‐Hilaire, 2002), but studies have not yet investigated which specific parental behaviors positively influence children's educational expectations. Our study demonstrates that expressing high expectations of success is an important way that parents positively impact their middle school students' beliefs that they will finish high school and go to college.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that parents affect their children's expectations through their own educational background, SES, and expectations for their children (Lowman & Elliott, 2010; St‐Hilaire, 2002), but studies have not yet investigated which specific parental behaviors positively influence children's educational expectations. Our study demonstrates that expressing high expectations of success is an important way that parents positively impact their middle school students' beliefs that they will finish high school and go to college.…”
Section: Discussionmentioning
confidence: 99%
“…The ELS is a nationally representative cohort study sponsored by the National Center for Educational Statistics (National Center for Educational Statistics, 2004). It includes multiple waves of student data; starting in the base year of 2002 when students were high school sophomores and concluding in 2012 when students were six years out of high school (see Bloom & Owens, 2013;Domina, 2009;Lowman & Elliott, 2010;& Museus & Vue, 2013 for additional analyses of the ELS data set).…”
Section: Data Source Sample and Proceduresmentioning
confidence: 99%
“…We also include demographic, background, and academic control variables that may confound relationships between anticipated family formation and educational expectations. Specifically, we control for age, year in school, mother's education, race/ethnicity, family structure, nativity, high school community type, grade point average (GPA), major, political ideology, and religious service attendance (Beal and Crockett ; Bohon, Johnson, and Gormon ; Crosnoe and Muller ; Feliciano and Lanuza ; Goyette ; Lowman and Elliott ; Morgan, Gelbgiser, and Weeden ; Mullen et al. ; Wells, Seifert, and Saunders ).…”
Section: Methodsmentioning
confidence: 99%
“…Expectations of educational attainment have risen over time in the United States in tandem with attainment itself. The overwhelming majority of high school students expect to earn a four‐year college degree, although, as of 2015, 33% of American adults 25 years of age and older held such a credential (Lowman and Elliott ; Ryan and Bauman ). Given high expectations and growing attainment, graduate or professional degrees have increasingly become the “passports” (Mullen et al.…”
Section: Educational Expectationsmentioning
confidence: 99%